The strategic role of total quality management in managing customer relationships/an applied study in the Pepsi Kufa factory - يوسف حجيم الطائي; هاشم فوزي دباس (Iraqi Journal for Administrative Sciences, 2024)
There are many topics that touch on total quality management, and this philosophy has become a concern for all organizations, which must be recognized and achieved in order to give them the opportunity to survive and grow. Therefore, the problem of this study came between two main axes, which are the strategic role of quality management on the one hand and customer relationship management on the other hand. Therefore, the problem of the study lies in answering the following questions: 1- Does the principle of focusing on the customer have a role in managing customer relationships? 2 - Does the principle of continuous improvement play a role in managing customer relationships? 3- Does the principle of focusing on the process have a role in managing customer relationships? Our study has a set of axes and basic points of importance that have been divided into three basic axes: The first axis: Importance at the customer level 1 - Highlighting the strategic role that the customer occupies in the strategic plans for quality at the organization level. 2- Knowing and measuring final customer satisfaction. Determine the benefits achieved for the customer that will achieve the ultimate value for him. 4- Knowing the degree of customer loyalty to the product offered by the organization. The second axis: Importance at the organization level: 1 - Identifying appropriate ways to retain the customer through studying satisfaction, loyalty and value). 2 - Determine general strategies, especially in the field of total quality management